2011
DOI: 10.1002/ijc.25770
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and risk of glioblastoma; evidence from the Melbourne collaborative cohort study

Abstract: Despite the brain being highly susceptible to the action of alcohol and, therefore, potentially susceptible to its carcinogenic effects, it is not clear whether alcohol consumption is associated with risk of glioblastoma. We analyzed data from 39,766 participants of the Melbourne Collaborative Cohort Study recruited in 1990-1994 and followed to the end of 2008 for an average of 15 years. Incidence of glioblastoma of the brain was ascertained via linkage to the Victorian and other State cancer registries in Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 25 publications
0
47
1
Order By: Relevance
“…In the Melbourne Collaborative Cohort study, alcohol was associated with the risk for developing Brought to you by | Oakland University Authenticated Download Date | 7/3/15 7:15 PM Risk factors for gliomas. An extensive review gliomas in a dose-response relation (81). But an older study from some of the members of the same team did not reveal any link between alcohol usage and gliomas (82).…”
Section: Lifestyle Factorsmentioning
confidence: 98%
“…In the Melbourne Collaborative Cohort study, alcohol was associated with the risk for developing Brought to you by | Oakland University Authenticated Download Date | 7/3/15 7:15 PM Risk factors for gliomas. An extensive review gliomas in a dose-response relation (81). But an older study from some of the members of the same team did not reveal any link between alcohol usage and gliomas (82).…”
Section: Lifestyle Factorsmentioning
confidence: 98%
“…In addition to age, a number of stress factors, including chemical exposure, and demographical aspects influence the incidence of tumor manifestation [7]. At least one study demonstrated an increased risk for glioblastoma by alcohol consumption [8]. When compared with other malignancies, modulation of immune suppressor effector cells appears to be of major importance [9], and individual tumor patients may require an individual treatment regimen against immune suppressive elements.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality registries were also used in some studies to ascertain additional cases (19,20,22,25,26,29,33,35). Follow-up rates exceeded 90% for 16 of 18 current studies (14,(37)(38)(39)(40)(41)(42) included in this analysis and is 80% for all studies (37)(38)(39)(40)(41)(42)(43)(44). We used the receptor status data from each study to define breast cancer subtypes by ER/PR status.…”
Section: Ascertainment Of Breast Cancer Casesmentioning
confidence: 99%